Geology and structure of Raniban–Champadevi area, Kathmandu valley, central Nepal - Acharya, KK; Dhital, MR (Journal of Nepal Geological Society, 2007)
The area between Raniban and Champadevi in the Kathmandu valley comprises the lower four formations (i.e. the Tistung Formation, Sopyang Formation, Chandragiri Limestone, and Chitlang Formation, respectively from bottom to top) of the Phulchauki Group belonging to the Kathmandu Complex. The rock sequence is represented by metasandstones, phyllites, slates, limestones, and dolomites. In several places, the rocks are covered either by fluvio-lacustrine sediments or alluvial fan deposits of the Kathmandu basin. The fan deposits are confined mainly to the foothills of the Chandragiri Range. Owing to intense deformation, the four formations are repeated and constitute five longitudinal folds, namely the Chhapdanda Syncline, Kirtipur Anticline, Naikap Syncline, Bhimdhunga Anticline, and Nagarjun Syncline from south to north, respectively. The folds plunge due SE and display sub-parallel axial traces. The two nearly vertical longitudinal faults, the Chobhar Fault and Baralgaun Fault, ramify the rock succession. Journal of Nepal Geological Society, 2006, Vol. 33 p.1-10